The Spatial Dynamics of Mouse-Tracking Reveal that Attention Capture is Stimulus-Driven Rather than Contingent upon Top-Down Goals - Dieciuc, Michael A. (J Exp Psychol Hum Percept Perform, 2019)
There has been a long-standing debate over why stimuli capture attention. Some argue that capture is driven by stimulus salience, while others believe that capture only occurs when the features of a stimulus match what we are searching for. This debate has recently focused on attentional disengagement, with the stimulus-driven camp claiming that all salient stimuli capture attention but attention is quickly disengaged from items dissimilar from our target, producing little cost in terms of response time. We used mouse-tracking to examine the spatial effect of cues that either matched or mismatched an observer’s target. Experiment 1 demonstrated that a cue mismatching the feature defining the target initially produced a spatial effect that was rapidly resolved, consistent with quick disengagement. Experiment 2 was a pre-registered replication with double the sample size that replicated the results of Experiment 1. Overall, computer mouse-tracking provided a direct observation of attentional disengagement, supporting stimulus-driven capture.